2019
DOI: 10.1145/3361128
|View full text |Cite
|
Sign up to set email alerts
|

Part-Time Ride-Sharing

Abstract: Ride-sharing companies have been reshaping the structure and practice of ride-hailing work. At the same time, studies have been showing mixed driver experiences on the platform while many of the drivers are working part-time. In this research, we seek to understand why drivers on this platform are working part-time, how this impacts their view of the platform, and what this means for more accurately evaluating the design of these platforms. To investigate this question, we focused on situating ride-sharing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…The authors describe how the platform and its design (1) heighten Ola drivers’ precarity while providing little benefits and (2) shift more customers from street-hailing to app-based hailing, which intensifies the drivers’ dependence of the platforms (Muralidhar et al 2022 ). Similarly, Ma and Hanrahan ( 2019 ) found that dependency on platform income heavily influenced Uber drivers’ attitude toward the platform and difficulties faced on the job. Schor et al ( 2020 ) emphasized this heterogeneity of the workforce in various platform companies as well as the disparate experiences of part-time and full-time gig workers.…”
Section: Methods: Systematic Literature Reviewmentioning
confidence: 97%
“…The authors describe how the platform and its design (1) heighten Ola drivers’ precarity while providing little benefits and (2) shift more customers from street-hailing to app-based hailing, which intensifies the drivers’ dependence of the platforms (Muralidhar et al 2022 ). Similarly, Ma and Hanrahan ( 2019 ) found that dependency on platform income heavily influenced Uber drivers’ attitude toward the platform and difficulties faced on the job. Schor et al ( 2020 ) emphasized this heterogeneity of the workforce in various platform companies as well as the disparate experiences of part-time and full-time gig workers.…”
Section: Methods: Systematic Literature Reviewmentioning
confidence: 97%
“…Further, regarding H4, where the enhancement generated by the combination of consumer community identification messages and negative framing is only significant for participation and quality approval, but not satisfaction, for simple tasks, it is possible that agents with more vs. less experience identify more strongly with the crowdsourcing platform due to their higher number of interactions over time. Ma and Hanrahan (2019) find some evidence of this, reporting that crowdsourced drivers who are heavily dependent on crowdsourcing income have higher use and interaction with the platform. Following this rationale, we explore the interaction effects of experience, measured by the number of jobs completed, as another independent variable, in lieu of being a control.…”
Section: Post Hoc Testsmentioning
confidence: 99%
“…Their advent has dramatically lowered the barriers to entry for participation in these labour markets and thus enabled job opportunities for all, albeit arguably at the expense of undermining the interests of full-timers (Rosenblat, 2018). In their study of 'part-time' ride-hailing drivers in the USA, Ma and Hanrahan (2019), however, argue that 'full-time' or 'part-time' classifications cannot be made merely based on the number of hours drivers spend working on a platform, but on how dependent they are on the earnings from it. Their study found that gig workers work for multiple platforms 'part-time' to make ends meet.…”
Section: Working For Ride-hailing Platformsmentioning
confidence: 99%
“…The peer-to-peer (P2P) exchange of goods, services and labour have received much attention in CSCW and HCI. Prior research has identified certain core issues with digital labour platforms, including the following: a) the modelling of workers as 'independent contractors' or as 'consumers of the platforms' technological services' (Rosenblat, 2018;Gray and Suri, 2019); b) precarious work conditions requiring 'part-time' workers to work on multiple platforms to make ends meet (Ma and Hanrahan, 2019); c) a neglect of workers' personal safety (Almoqbel and Wohn, 2019); and d) problems with evaluation mechanisms, which often create power imbalances (Lee et al, 2015;Rosenblat and Stark, 2016). The information asymmetries around critical aspects of work such as task assignment coupled with a lack of control over wage determination and lack of adequate grievance redressal mechanisms have been shown to disenfranchise workers (Gupta et al, 2014;Ahmed et al, 2016;Hanrahan, Ma, and Yuan, 2017;Rosenblat, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation